Neurotoxocariasis: a little-known manifestation of a neglected zoonosis - Chieffi, Pedro Paulo; Rodrigues e Fonseca, Gabriela; Diniz Cabral, Aline; Vieira dos Santos, Sergio (Revista de Patologia Tropical / Journal of Tropical Pathology, 2025)
This review covers general aspects of the occurrence of toxocariasis as a parasitic zoonosis, with a focus on neurotoxocariasis, a form of human infection that is still poorly understood and under-studied. The main aspects of manifestations resulting from the involvement of the central nervous system (CNS) in experimental animals and humans are discussed, with an emphasis on the difficulties in establishing a precise laboratory diagnosis of this infection, as well as the existing therapeutic challenges. KEY WORDS: Neurotoxocariasis; toxocara canis; toxocara cati.